Sentence with Multiple Clauses Found in the Reading Section Passages of TOEFL Longman Complete Test - Anggun Purnomo Arbi (P-SEMART JOURNAL, 2021)
Analysis of sentences with multiple clauses has an essential role in the process of learning English. This study had a purpose to describe the types of sentence with multiple clauses. In supporting this study, the researcher used theories of sentence with multiple clauses by Deborah Phillips. This study was a type of descriptive qualitative study as it analyzed the word data. The object of this study was the text of reading section question of TOEFL Longman Complete Test written in the book ‘Longman Complete Course for the TOEFL Test’. Documentation was the step of collecting data in this study. Data analysis of this study was identifying the sentence with multiple clauses, classifying the types of sentence with multiple clauses, and describing all the results. the researcher found 18 sentences categorized as the sentences with multiple clauses. Those sentences were divided into three types: noun clause (2 sentences), adjective clause (11 sentences), and adverb clause (5 sentences).